Increasing saltiness perception and keeping properties of low salt bread using inhomogeneous salt distribution achieved with salt agglomerated by waxy starch - Monteiro, Antonio Roberto Giriboni (2021)
This study aimed to evaluate the effect of using salt agglomerates produced by waxy starch, inhomogenously distributed, on the quality parameters and saltiness perception of bread with reduced sodium content. Three treatments were carried out: control, salt content reduced by 30%, and salt content reduced by 30% with salt randomly added as agglomerates. The technological characteristics of the dough (alveograph and farinograph) and the characteristics of the bread: specific volume, texture profile, colour (L*, a*, b*), and saltiness perception were evaluated. The utilization of the salt agglomerates kept almost all the quality parameters of the dough. There was only a slight increase in dough development time and a decrease in dough stability, which have been already found in previous studies with a salt reduction in bread. Furthermore, in the salt agglomerates essay, the perception of saltiness increased, resulting in bread with 30% salt reduction but similar to the control. It can be concluded that the use of salt agglomerates made with waxy starch and added in inhomogeneous distribution can improve the saltiness perception of bread without affecting the quality parameters